Guide to the literaty analysis for senior students in high school - Guerra, Karen (UDELAS, 2011)
During the development of this project, we have focused in needs, interests and skills of the students through a series of interesting aand fun activities such as role play, cause and effect game, comprehension spinner, persuasion activity and others in order to motivate them to interact with each other and literature readings.